2018
DOI: 10.1096/fj.201801104r
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing simvastatin as a therapy for preterm labor: evidence from preclinical models

Abstract: Preterm birth (PTB), the leading cause of neonatal morbidity and mortality, urgently requires novel therapeutic agents. Spontaneous PTB, resulting from preterm labor, is commonly caused by intrauterine infection/inflammation. Statins are well-established, cholesterol-lowering drugs that can reduce inflammation and inhibit vascular smooth muscle contraction. We show that simvastatin reduced the incidence of PTB in a validated intrauterine LPS-induced PTB mouse model, decreased uterine proinflammatory mRNA conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 78 publications
(110 reference statements)
1
23
0
Order By: Relevance
“…The normal time to delivery for C57Bl/6J mice from the morning of day 17 gestation is~60 h; therefore, we set parameters for induction of PTB as delivery ≤48 h post-bacterial inoculation, which was performed in the morning of day 17 (consistent with previous studies examining LPS-induced PTB 41,42 ). PTB rates for N-9-pre-treated UP-infected animals (N-9 + UP) were increased (10/36; 28%; P = 0.0104, Fisher's exact test) compared to animals receiving PBS and sterile USM ( preterm born pups (vaginally delivered) were found alive during twice daily cage checks.…”
Section: Resultsmentioning
confidence: 99%
“…The normal time to delivery for C57Bl/6J mice from the morning of day 17 gestation is~60 h; therefore, we set parameters for induction of PTB as delivery ≤48 h post-bacterial inoculation, which was performed in the morning of day 17 (consistent with previous studies examining LPS-induced PTB 41,42 ). PTB rates for N-9-pre-treated UP-infected animals (N-9 + UP) were increased (10/36; 28%; P = 0.0104, Fisher's exact test) compared to animals receiving PBS and sterile USM ( preterm born pups (vaginally delivered) were found alive during twice daily cage checks.…”
Section: Resultsmentioning
confidence: 99%
“…Except for introduction of LPS into the endocervix (144), which breaches the luminal epithelial immune interface, there is consistent evidence for systemic inflammatory drive of preterm birth. By example, the importance of myeloid-derived immune cells and activities for cervix remodeling was emphasized in a recent study in mice that used antibody treatment to suppress the cytokine granulocyte-macrophage colony stimulating factor (GM-CSF) and block LPS-induced preterm birth (145). GM-CSF acts to reduces myeloid cell migrations, stimulates their differentiation, and proinflammatory activities (146).…”
Section: Immunobiologic Perspective On Cervix Remodeling With Pretermmentioning
confidence: 99%
“…The common use of mice to investigate inflammation-induced preterm parturition has also served as a model to study the effects of a variety of agents to block preterm birth. By example, the effects of LPS to induce preterm birth can be blocked by systemic or intravaginal treatments with a variety of anti-inflammatory agents (145,147,148). Although effects of these or related compounds on cervix remodeling have yet to be studied, the implication is that, like GM-CSF, actions may be upon upstream mechanisms related to myeloid cell phenotypic actions in the final common pathway for parturition.…”
Section: Immunobiologic Perspective On Cervix Remodeling With Pretermmentioning
confidence: 99%
“…Indeed, we have shown that cathelicidin can promote pulmonary clearance of Pseudomonas aeruginosa in an in vivo murine model by enhancing the neutrophil response 13 . In our murine LPS-induced PTB model, intrauterine LPS injected Camp −/− mice, compared to wild type mice, showed significantly less circulating maternal IL-6; a pro-inflammatory cytokine shown to increase in myometrial cells after LPS stimulation 32 and known to play an important role in the development of preterm and term labour 3335 . This may suggest that mCRAMP influences the inflammatory profile to some extent and may have the potential to trigger the inflammatory cascade that ultimately leads to labour (Fig.…”
Section: Discussionmentioning
confidence: 78%